TLR4 as a therapeutic target: Antidepressant mechanism of saikosaponin A in regulating the NF-κB/BDNF axis and mitigating oxidative stress and inflammation in vivo and in vitro - Tan, Lin; Li, Jiayue; Sun, Dingcheng; Tian, Xinyi; Zhong, Xiaoli; Shan, Yiyi (Frontiers in Pharmacology, 2025)
Natural plant-derived active ingredients have gained increasing attention for their potential in the treatment of depression due to their safety and multi-target pharmacological activities. Saikosaponin A (SSA), a major bioactive saponin extracted from Bupleurum (a medicine and food homologous plant), has been reported to possess anti-inflammatory, neuroprotective, and antioxidative properties. In this study, we evaluated the antidepressant-like effects of SSA in a mouse model of chronic unpredictable mild stress (CUMS)-induced depression. Mice were subjected to CUMS, followed by daily administration of SSA (20 mg/kg, po for 6 weeks). Behavioral tests, including tail suspension test, open field test, elevated plus maze, and marble burying test, indicated that SSA significantly alleviated depressive-like and anxiety-like behaviors. Histopathological analysis by H&E staining showed that SSA reduced hippocampal neuronal damage induced by chronic stress. Biochemical assays revealed that SSA normalized levels of neurotransmitters (5-HT, DA, and 5-HIAA), enhanced antioxidant enzyme activity (SOD, CAT, and GSH), and suppressed neuroinflammatory cytokine production (TNF-α, IL-1β, and IL-6). Mechanistically, SSA exerted its antidepressant effects by inhibiting the TLR4/NF-κB signaling pathway and upregulating BDNF expression. In PC12 cells, TLR4 overexpression attenuated SSA’s protective effects, whereas TLR4 silencing enhanced cellular resistance to corticosterone-induced damage. These findings suggest SSA alleviates CUMS-induced depression-like behaviors in mice by modulating neuroinflammation and oxidative stress through the TLR4/NF-κB/BDNF signaling axis, indicating its potential as a functional food-derived therapy for depression.